2020
DOI: 10.1186/s12870-020-02429-w
|View full text |Cite
|
Sign up to set email alerts
|

Complete chloroplast genomes of four Physalis species (Solanaceae): lights into genome structure, comparative analysis, and phylogenetic relationships

Abstract: Background Physalis L. is a genus of herbaceous plants of the family Solanaceae, which has important medicinal, edible, and ornamental values. The morphological characteristics of Physalis species are similar, and it is difficult to rapidly and accurately distinguish them based only on morphological characteristics. At present, the species classification and phylogeny of Physalis are still controversial. In this study, the complete chloroplast (cp) genomes of four Physalis species (Physalis ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 65 publications
16
37
0
Order By: Relevance
“…It had four more genes (ycf2, rpl23, rpl2, and trnI-CAU) than seven other Ligusticum species in IRa, which was likely ascribed to the gene duplication resulting from the extensions of IRs. The varied gene number in the congeneric species has been found in other angiosperm plastomes [31,32]. For L. delavayi, the IRa/LSC border was rpl2/trnH genes and the LSC/IRb border was rps19/rpl2 genes, which were different from seven other Ligusticum species (trnL/trnH and ycf2).…”
Section: Plastome Evolutionmentioning
confidence: 80%
“…It had four more genes (ycf2, rpl23, rpl2, and trnI-CAU) than seven other Ligusticum species in IRa, which was likely ascribed to the gene duplication resulting from the extensions of IRs. The varied gene number in the congeneric species has been found in other angiosperm plastomes [31,32]. For L. delavayi, the IRa/LSC border was rpl2/trnH genes and the LSC/IRb border was rps19/rpl2 genes, which were different from seven other Ligusticum species (trnL/trnH and ycf2).…”
Section: Plastome Evolutionmentioning
confidence: 80%
“…In concordance with the present study, Hu et al [57] reported a closer phylogenetic relationship between P. floridana and P. peruviana than between P. peruviana with P. philadelphica using chloroplast markers. Similarly, a recent study that used complete chloroplast genomes conducted by Fen et al [58] identified a close similarity between P. angulata and P. peruviana genomes. Both results were found in the NJ and PCA analyses reported in this study (Figs 2 and 3).…”
Section: The Standardized Gbs Pipeline Allowed To Differentiate the Pmentioning
confidence: 74%
“…Similarly, a recent study that used complete chloroplast genomes conducted by Fen et al . [ 58 ] identified a close similarity between P . angulata and P .…”
Section: Discussionmentioning
confidence: 99%
“…2). The number of SSR in the Santalum chloroplast genome was low compared to photoautotrophic plant lineages [31][32][33][34].…”
Section: Santalum Chloroplast Genome Evolution and Variationmentioning
confidence: 93%